Etawa Crossbreed Goat Leukocyte Profile After Infusion of Moringa oleivera Leaf - Fahrodi, Deka Uli; Said, Nur Saidah; Gading, Besse Mahbuba We Tenri; Sukoco, Hendro (Universitas Halu Oleo, 2023)
This study aims to determine the potential of Moringa oleivera leaf infusion as an immunomodulator in Etawa Crossbreed goats. The experimental animals used were 25 Etawa Crossbreed goats aged 8-9 months and divided into 5 treatments, namely: P0 (100% distilled water); P1 (5% Moringa oleivera leaf infusion); P2 (10% Moringa oleivera leaf infusion); P3 (15% Moringa oleivera leaf infusion) and P4 (20% Moringa oleivera leaf infusion). The results showed that the total leukocytes before treatment showed no significant difference between treatments (P>0.05), while after treatment, there was a significant difference between treatments (P